Biosourced terpenoids for the development of sustainable acrylic pressure-sensitive adhesives via emulsion polymerisation. Issue 14 (25th June 2020) - Droesbeke, Martijn A.; Simula, Alexandre; Asua, José M.; Du Prez, Filip E.
Abstract : Terpenoid-based (meth)acrylates are introduced in waterborne acrylic pressure-sensitive adhesives via emulsion polymerization. These materials showed good tack, peel strength and shear resistance properties, comparable to a petroleum-based benchmark. Abstract : The increasing regulations and restrictions in favour of a biobased and sustainable community could potentially harm the strong economic position of the polymer industry, which still heavily relyies on crude oil. The adhesive industry, in particular, is looking for more renewable alternatives and more environmentally friendly synthesis routes. In this work, (meth)acrylate derivatives of terpenoids, namely tetrahydrogeraniol, citronellol, menthol and isoborneol are introduced in the synthesis of waterborne pressure-sensitive adhesives (PSA) based on acrylic latexes via emulsion polymerisation. This industrially implemented setting enables the preparation of five different formulations with high biobased content with a renewable carbon content ranging from 70 to 100%. The biobased PSAs are found to be comparable in terms of tack, peel strength and shear resistance to a benchmark petroleum-derived commercial product. They show good adhesion properties on steel, glass and polyethylene surfaces. Moreover, the various formulations displayed different mechanical and adhesion properties, which make them attractive for a wide range of applications.